2020
DOI: 10.1089/neu.2019.6510
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Histopathological Damage Occurring Up to One Year after Experimental Traumatic Brain Injury Is Associated with Cognitive Decline and Depression-Like Behavior

Abstract: Increasing clinical and experimental evidence suggests that traumatic brain injury (TBI) is associated with progressive histopathological damage. The aim of the current study was to characterize the time course of motor function, memory performance, and depression-like behavior up to 1 year after experimental TBI, and to correlate these changes to histopathological outcome. Male C57BL/6N mice underwent controlled cortical impact (CCI) or sham operation, and histopathological outcome was evaluated 15 min, 24 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 103 publications
2
9
0
2
Order By: Relevance
“…Of note, the present study assessed an early time-point after TBI that is very commonly used in experimental TBI studies. As it is becoming more and more obvious that TBIinduced brain damage evolves over much longer periods than previously thought (Mao et al 61 ), potential long-term effects of NMP will have to be evaluated. Hence, additional studies need to be performed to further characterize its effects on long-term lesion progression and its mechanisms of action.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the present study assessed an early time-point after TBI that is very commonly used in experimental TBI studies. As it is becoming more and more obvious that TBIinduced brain damage evolves over much longer periods than previously thought (Mao et al 61 ), potential long-term effects of NMP will have to be evaluated. Hence, additional studies need to be performed to further characterize its effects on long-term lesion progression and its mechanisms of action.…”
Section: Resultsmentioning
confidence: 99%
“…For example, many reports describe an increase in depressive-like behavior in models of TBI, in good accordance with the clinical studies. The most convincing hallmark of those reports is the concurrence of the depressive-like phenotype, which is recognized despite the fact that these studies are being handled in different institutes using a wide range of parameters, such as age, animal species, injury models, severity of injury and time post-injury 100,101,[114][115][116][117][118][119] . Therefore, these findings suggest that depression is a robust consequence of TBI.…”
Section: Relevance Of Pre-clinical Models Of Tbi To Human Ctementioning
confidence: 99%
“…NP (Munich, Germany) showed that controlled cortical impact in adult mice induces progressive cognitive decline (Mao et al, 2020). While motor function recovered partially after TBI, depression-like behavior and the loss of memory function were progressive.…”
Section: Traumatic Brain Injury Can Lead To Cerebrovascular Diseasementioning
confidence: 99%